Shear wave elastography: Can it be a new radiologic approach for the diagnosis of erectile dysfunction?. (August 2017) - Turkay, Rustu; Inci, Ercan; Yenice, Mustafa Gurkan; Tugcu, Volkan
Introduction: Erectile dysfunction (ED) is a common health problem among males, and radiology has limited use in its diagnosis and treatment. Shear wave elastography (SWE) is a new sonographic technique. In this study, we examined the significance of SWE in the diagnosis of ED. Methods: The study included a total number of 70 participants. The mean age of the participants was 54.14 ± 8.03 years (range: 39 and 71 years old). We composed two groups. Group 1 had 35 patients who presented to the urology clinic in our hospital complaining of ED, and had a score of 17 or lower from the International Index of Erectile Function (IIEF) questionnaire. Group 2 consisted of 35 healthy volunteers who did not have ED. SWE measurements were performed from corpus cavernosum penis in both groups, and the results were noted. Differences between the groups were evaluated statistically. Results: The difference between the mean SWE measurements of two groups (Group 1: 20.94 ± 6.23 kPa and group 2: 24.63 ± 7.58 kPa) was found to be statistically significant ( p = 0.027; p < 0.05). For a cut-off value of 17.1 kPa, the SWE method has specificity, sensitivity, positive predictive value, and negative predictive value regarding diagnosis of ED as 94.29%, 34.29%, 85.71%, and 58.93%, respectively. The mean age of the groups did not show a statistically significant difference ( p = 0.287; p > 0.05). Conclusions: Due to its high specificity and positive predictive value, SWE can offer useful data in the radiologic evaluation of ED cases.